Influence of Water-Structure and Soil-Structure Interaction on Seismic Performance of Sea-Crossing Continuous Girder Bridge - Jie Guo; Kunpeng Wang; Hongtao Liu; Nan Zhang (Advances in Civil Engineering)
Based on the Hong Kong-Zhuhai-Macao project, considering the fluid-structure interaction and soil-structure interaction, the seismic response of a sea-crossing continuous girder bridge is analyzed. Three-dimensional nonlinear numerical bridge model is developed, in which the hydrodynamic force is represented by added mass and pile-soil interaction is represented by p-y elements. Meanwhile, stratification of soil is considered in the free field analysis. Through the comparison of responses of the bridge cases, the effects of earthquake-induced hydrodynamic force and pile-soil interaction are studied. For the influence of hydrodynamic force, the results show that it is relatively slight as compared with pile-soil interaction; moreover pile foundation is more sensitive to it than other bridge components. The influence of pile-soil interaction is relatively significant. When both of the interactions are considered, the influence is not a simple superposition of acting alone, so it is recommended to consider both factors in dynamic analysis.